Implementation of the Function for User Program Execution Control in the Windows Environments - Ju, Jang Senng (IJRDO -Journal of Computer Science Engineering, 2016)
In this paper, we design a program that controls the execution permissions for the running application in the Windows system environment. It does not allow general users to execute the program converting the specific location information of the execution program, to any of the bit values with the formal structure information in window program. The converted bit value can be returned to the original bit value in the case of an authorized user, so that the original program can be normally performed. By doing so, it can be more safely used in the risk of reverse engineering for Windows executable program. We implemented the control program for the program execution authority we proposed in this paper, and the experiment was performed. At the results of experiments, it was confirmed that the control function to permit execution for the user program was working properly in the Windows environment.